Niveles séricos de hierro comparados provenientes de hígado frito de bos taurus l. y tabletas genéricas de sulfato ferroso - Calderón Rodríguez, Harold Dante (2008)
We compared iron serum levels originating from fried liver of Bos taurus L. and generic ferrous sulphate tablets. Using the method of Iron - Ferrozina of BioSystems. The study was made in 16 apparently healthy volunteers. They in the first period ingested 300g of fried liver from Bos taurus L. and in the second period a ferrous sulphate tablet was administered by oral route (300mg), we made determinations to 30 min, 1 hour, 2 hours, 4 hours, 6 hours and 8 hours in both periods respectively previous taking of a basal sample. The concentrations average obtained for the fried liver of Bos taurus L. were: 30 min (179.90 ug/dl), 1 hour (381.59 ug/dl), 2 hours (500.57 ug/dl), 4 hours (464.59 ug/dl), 6 hours (252.53 ug/dl) and 8 hours (165.17 ug/dl). For ferrous sulphate tablets were: 30 min(27.75 ug/dl), 1 hour (83.22 ug/dl), 2 hours (128.65 ug/dl), 4 hours (301.12 ug/dl), 6 hours (438.23 ug/dl) y 8 hours (266.59 ug/dl). Of the obtained results there concludes that: the ingestion of liver fried of Bos taurus L. had a fast absorption and a high iron serum levels, in comparison with the ferrous sulphate tablets